Teaching students in math circles to solve certain equations by bringing them into a system of equations. - A.Turgunov; M.Askaraliyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes how to solve some equations in a system of equations of equal strength, and gives examples of their solutions.